Issues of legal regulation of the testament form: comparative-legal analysis - Nukusheva, A.A. (Bulletin of the Karaganda University “Law Series”, 2021)
Under the transition of the Republic of Kazakhstan to the market economy, conducting reforms to expand the range of private property objects and, accordingly, the growth of interest in the methods of determining the predestination of property upon the death of the owner, the institute of testamentary succession is given a special role in Kazakhstan’s society. The question of in what legal form today it is possible to make an order in case of death determines the subject of this study. With the help of a comparative-legal method an analysis of the existing legislative framework of the Republic of Kazakhstan was carried out, including the study of acts of international legislation in the sphere of hereditary law. In addition, the article addresses how modern international initiatives in the sphere of legal regulation of inheritance in the will are developing; the offers for the improvement of Kazakhstan legislation in the expansion of admissible forms of testament are considered. The author has expressed a proposal for conducting the existing legislation of the Republic of Kazakhstan norm, which allows the drawing up of a testament in the form of video. The author determines the concept, main types and forms of the testament, explores the features of the forms of testament in the legislation of the Republic of Kazakhstan, CIS countries and a number of other countries. The article establishes the need for further improvement of Kazakhstani legislation in the sphere of expanding the permissible forms of the testament. Based on the analysis of the current legislation of the Republic of Kazakhstan, the CIS countries and a number of other states, the author comes to the conclusion that the form of presentation of the devisor established by law is an undeniable unconditional guarantee of the execution of his will. In a practical aspect, this research is of interest to lawyers practicing in the sphere of civil law, as well as international private law.